2017
DOI: 10.1080/20932685.2017.1399083
|View full text |Cite
|
Sign up to set email alerts
|

Enabling the digital fashion consumer through fit and sizing technology

Abstract: Online fashion retailing is a major growth area. Innovative online fit and sizing technologies that facilitate purchase continue to develop and launch, however, problems associated with digital expectations of fit and size in consumer decision-making, remain unresolved. This research focuses on 20 prominent fit and size technologies from a sample of 30, and uses content analysis to examine website design and operation. Content analysis combined with an extended literature review enables the linking of academic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 50 publications
2
32
0
Order By: Relevance
“…Social shopping platforms support user-generated content and user interactions, in contrast to the traditional shopping practices of e-commerce where consumers shop individually (Zhang and Benyoucef, 2016;Vazquez et al, 2020). Social shopping advances have challenged fashion marketers to modernise marketing practices by developing a range of user-generated social shopping activities to increase consumer interaction via sharing of user generated content (UGC) in blog style platforms (Jin and Ryu, 2019;Hollebeek, 2019;Connell et al, 2019;Liu et al, 2016;Dulabh et al, 2017;Miell et al, 2018). A notable characteristic of fashion UGC is "Looks" features, which are defined as photographs of individuals in a styled setting (McQuarrie et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Social shopping platforms support user-generated content and user interactions, in contrast to the traditional shopping practices of e-commerce where consumers shop individually (Zhang and Benyoucef, 2016;Vazquez et al, 2020). Social shopping advances have challenged fashion marketers to modernise marketing practices by developing a range of user-generated social shopping activities to increase consumer interaction via sharing of user generated content (UGC) in blog style platforms (Jin and Ryu, 2019;Hollebeek, 2019;Connell et al, 2019;Liu et al, 2016;Dulabh et al, 2017;Miell et al, 2018). A notable characteristic of fashion UGC is "Looks" features, which are defined as photographs of individuals in a styled setting (McQuarrie et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Lenient return policies promote physical fit verification, since customers can verify the fit of the product at home, but this important fit verification activity could also occur earlier Retail supply chain costs of product returns in the customer's process, even before they place the order, and as such, reduce the number of returns and, subsequently, costs. Advanced technologies provide authentic fit information, and research has pointed to the use of digital product fitting using 3D scanning to create a digital model of the customer and product for recommending fitting products (Gustafsson et al, 2019;Miell et al, 2018), potentially enabling virtual fit verification. Previous research has proposed virtual try-ons and interactive trial rooms for customers to assess the fit of a product (Liu et al, 2017;Misra and Arivazhagan, 2017); however, such applications rely on standard customer models (avatars), which only provides the customer with fit information, since without actual body scanning data, the visualization may not realistically represent the fit.…”
Section: Pre-sales Fit Uncertainty Mitigation Practicesmentioning
confidence: 99%
“…To support customers ordering fit-dependent products online, retailers can apply different technologies to webshops to make fit more comprehensible for customers (Gustafsson et al , 2019; Miell et al , 2018); these range from the most basic size chart converter to more advanced technologies that provide virtual fit verification. However, while size charts are easy to implement, their accuracy is questionable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the potential impacts of whole-body scanning on body satisfaction are unclear, and no studies to date have investigated the impact of whole-body scanning on women's body image in a controlled experiment. This has important implications because of the wide use of this technology in the clothing environment and the increased use of the real body and its realistic visualization in virtual fitting (Gill, 2015;Januszkiewicz, Parker, Hayes & Gill, 2017;Miell, Gill, & Vazquez, 2018). The study reported here investigates impacts of scanning on women's body satisfaction using a well-controlled experimental design where women are exposed to body scanning and impacts on body image are compared against a control group of women not exposed to body scanning.…”
Section: Whole Body Scanning As a Tool For Clothing Sizing: Effects Omentioning
confidence: 99%